Mini-Bentall procedure - Yan, Tristan D. (Annals of Cardiothoracic Surgery, 2015)
An important goal in cardiovascular and thoracic surgery is reducing surgical trauma to achieve faster recovery for our patients. Mini-Bentall procedure encompasses aortic root and ascending aortic replacement with re-implantation of coronary buttons, performed via a mini-sternotomy. The skin incision extends from the angle of Louis to the third intercostal space, usually measuring 5-7 cm in length. Through this incision, it is possible to perform isolated aortic root surgery and/or hemi-arch replacement. The present illustrated article describes the technical details on how I perform a Mini-Bentall procedure with hemi-arch replacement.